KOMPARASI EFISIENSI PENGGUNAAN TRAKTOR, TERNAK KERBAU DAN TENAGA MANUSIA DALAM PENGOLAHAN LAHAN USAHATANI PADI - Tedi Hartoyo; M Iskandar Mamoen; Hendar Nuryaman (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
This study aims to develop a capacity analysis, the cost analysis and comparative efficiency of use of the tractor, buffalo and power man in the processing of paddy farmland. The study was conducted using survey method in the city of Tasikmalaya. Based on the analysis, of this study concluded there are significant differences amount of capacity, the cost of the use of tractor, livestock and human labor in the processing of farm land. Tractor in land processing, achieve the highest capacity 0.0425 ha/hour compared with 0.0292 ha/hour the buffalo capacity and manpower 0.0021 ha/hour For using the land with the highest human power Rp 1.610.227/ha, and the lowest cost using Rp 364.127 cattle /ha, while the cost of the use of tractor is between them, namely Rp 715.390 /ha. Based on the capacity and the cost can be stated that it is technically the most efficient use of tractor, but economically use the most efficient buffalo shows.